Tourism, Water Pollution, and Waterway Landscape Changes in a Traditional Village in the Huizhou Region, China - Pinyu Chen; Yizheng Zhao; Di Zuo; Xiang Kong (Land, 2021)
Based on archival research, non-participatory observation, and semi-structured interviews, this paper examined waterway landscape changes mainly caused by tourism development in Hongcun, a traditional village in the Huizhou region, China, and how the locals have responded to water pollution in order to achieve landscape sustainability. It is found that the physical structure of the waterways of Hongcun Village has been well preserved, but the water pollution caused by tourism, with a combination of changes of land use and demographic structure, has changed the functions and cultural meanings of waterways. Although there remains quite a daunting task towards sustainability in terms of technology, heritage protection, and desire for development, we claim the waterways environmental governance in which local governments play a crucial role in resilience strategies by controlling the sewage from homestays, restaurants, and pigment sewage from sketches. However, the ways in which landscape animates, including the daily lives, processual daily practices, and mundane activities of different social actors related to waterways, deserve further implementation to build the resilience of cultural landscape from the perspective of non-representational theory. This paper adds to a new narrative to the waterway landscape research by presenting a water utilization pattern that could profitably coexist with a specific environment in the Huizhou region in the agricultural society of ancient China and discussing how the non-representational theory contributes to analyzing and managing waterway landscapes in modern times. It also sheds light on the connection between cultural landscape and resilience.